2013
DOI: 10.1371/journal.pntd.0002050
|View full text |Cite
|
Sign up to set email alerts
|

Mosquito Cellular Factors and Functions in Mediating the Infectious entry of Chikungunya Virus

Abstract: Chikungunya virus (CHIKV) is an arthropod-borne virus responsible for recent epidemics in the Asia Pacific regions. A customized gene expression microarray of 18,760 transcripts known to target Aedes mosquito genome was used to identify host genes that are differentially regulated during the infectious entry process of CHIKV infection on C6/36 mosquito cells. Several genes such as epsin I (EPN1), epidermal growth factor receptor pathway substrate 15 (EPS15) and Huntingtin interacting protein I (HIP1) were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 70 publications
5
49
0
1
Order By: Relevance
“…Our results are in line with an earlier study of Bernard et al, who showed that CHIKV infection of HEK-293T cells is dependent on the integrity of early endosomes, but not on late endosomes (28). In mosquito cells, both early and late endosomes are required for CHIKV infection, suggesting that in these cells, CHIKV is trafficked to maturing/late endosomes before fusion (32). This discrepancy may be related to the different virus strains used but could also be related to potential differences in the endosomal pH between cells (64).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are in line with an earlier study of Bernard et al, who showed that CHIKV infection of HEK-293T cells is dependent on the integrity of early endosomes, but not on late endosomes (28). In mosquito cells, both early and late endosomes are required for CHIKV infection, suggesting that in these cells, CHIKV is trafficked to maturing/late endosomes before fusion (32). This discrepancy may be related to the different virus strains used but could also be related to potential differences in the endosomal pH between cells (64).…”
Section: Discussionsupporting
confidence: 93%
“…The observation that CHIKV enters cells via CME is in line with two earlier reports on CHIKV cell entry (31,32). In these studies, significant inhibition of viral infectivity was seen in cells treated with drugs or siRNAs that have been proposed to interfere with CME.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A detailed entry mechanism description is not available so far. Some authors implicate a clathrin-dependent pathway [64,66], whereas other authors have proposed that CHIKV enters by a clathrin-independent, but Eps15-dependent pathway [65]. These later authors also have found evidence that multiple pathways maybe employed by CHIKV to enter into cells, as already proposed with dengue virus (DENV) [67,68].…”
Section: Genomic Organization and Viral Replicationmentioning
confidence: 94%